Analisis Penamaan Diri Mahasiswa Kelas 6A Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Riau - Azka Febrianti; Rahmat Fernando Yulistyo Syaputra; Septri Anjarini; Tasya Nidea Putri (UIR Press, 2023)
This study uses a descriptive method which is an explanation based on existing facts so as to produce an explanation as to what the Islamic University of Riau is a university in the city of Pekanbaru which has interesting meanings in the names of its students. Based on the analysis findings, there are naming elements from Javanese language and culture, naming using Arabic foreign language elements, and from the combined elements of parental or descendant names in the name. This is the basis for studying, especially those related to the language elements and meanings contained in the names of the sixth semester Indonesian Language Study Program students at the Islamic University of Riau. Understanding the language of these elements and types of meaning can be known based on language as an element forming student names and the types of meanings contained in them. The data is processed using a data analysis table according to the formulation of the problem presented in the study, such as the elements of self-naming and the type of meaning of self-naming. Furthermore, a description is carried out using an explanation that is explained using sentences (qualitative) in the study.